INTERNALISASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK AKHLAKUL KARIMAH SANTRI PONDOK PESANTREN AL HIKMAH TUBAN - Moch. Shohibul Husni; Muhammad Walid; Indah Aminatuz Zuhriah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2023)
Internalization of Islamic religious values is very important for the formation of attitudes and behavior of students, especially for teenage students. In this era of globalization, it is feared that children will have attitudes and behaviors that are not commendable if they are not accustomed to the internalization of Islamic religious values from an early age. This study aims to describe how the process of internalizing Islamic religious values in the formation of Akhlakul Karimah students at the Al Hikmah Binangun Singgahan Islamic Boarding School, Tuban, and to describe the success of the process of internalizing Islamic religious values in the formation of Akhlakul Karimah students at the Al Hikmah Binangun Islamic Boarding School, Singgahan Tuban . The research was conducted at the Al Hikmah Islamic Boarding School which is located in the village of Binangun, Singgahan District, Tuban Regency, East Java. This research uses a qualitative approach with a case study type. Data collection was carried out using interviews, observation, and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The research results obtained are as follows. The process of internalizing the values of Islamic religious education to form Akhlakul Karimah at the Al Hikmah Islamic boarding school has 3 stages, namely the introduction stage, the acceptance stage and the integration stage. The curriculum programmed by PP. Al Hikmah in learning to support internalization is by Reciting the Book, Madrasah diniyah with 3 levels, Reciting the Qur'an, and. Bahtsul Masa'il. The method applied by PP. Alhikmah in internalizing the values of Islamic religious education namely Bandongan, Questions and Answers, Exemplary, Habituation, Discipline Strategy. The results of internalizing the values of Islamic religious education in forming ahklakul karimah are responsibility, independence, social spirit.